Using games as a motivational strategy to improve writing skills among students of second year “a” of bachillerato, afternoon session at unidad educativa Manuel Ignacio Monteros Valdivieso, in the city of loja during the 2018 – 2019 school year - Cajamarca Gordillo, Erika Janela (2020)
The main objective of the research was to improve writing skills through the application of games among students of second year “A” of Bachillerato, at Unidad Educativa Manuel Ignacio Monteros in the city of Loja during the 2018-2019 school year. The scientific, the descriptive, the statistical, and the analytic-synthetic methods were selected to find theoretical information about games, describe the stages of study, interpret and represent the results obtained in the research. Data was collected through tests and questionnaires applied to 18 students. Likewise, observation sheets and field notes were useful to record students’ progress and attitudes. The students had a meaningful improvement in writing skills which was excellent in the five indicators: nouns, adjectives, verbs, spelling and transitions words. The application of games helped students to feel more comfortable and collaborative in classes, also they promoted the students’ cooperation, and motivated them to participate more actively in the classroom.